2021
DOI: 10.1136/bmjopen-2020-044102
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the SARS COVID-19 pandemic and critical care resources threshold in the Gulf Cooperation Council (GCC) countries: population analysis of aggregate data

Abstract: ObjectiveTo generate cross-national forecasts of COVID-19 trajectories and quantify the associated impact on essential critical care resources for disease management in Gulf Cooperation Council (GCC) countries.DesignPopulation-level aggregate analysis.SettingBahrain, Kuwait, Oman, Qatar, United Arab Emirates (UAE) and Saudi Arabia.MethodsWe applied an extended time-dependent SEICRD compartmental model to predict the flow of people between six states, susceptible–exposed–infected–critical–recovery–death, accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, it has been reported that enteral addition of l ‐glutamine in the early period of SARS‐CoV‐2 infection could lead to a shortened hospital stay and less need for ICU admission. [ 25–27 ] Collectively, we revealed that metabolic profiles were similar between asymptomatic patients and symptomatic patients in remission, and identified l ‐citrulline, l ‐glutamine, and l ‐alanine as the commonly up‐regulated metabolites among these groups.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, it has been reported that enteral addition of l ‐glutamine in the early period of SARS‐CoV‐2 infection could lead to a shortened hospital stay and less need for ICU admission. [ 25–27 ] Collectively, we revealed that metabolic profiles were similar between asymptomatic patients and symptomatic patients in remission, and identified l ‐citrulline, l ‐glutamine, and l ‐alanine as the commonly up‐regulated metabolites among these groups.…”
Section: Resultsmentioning
confidence: 91%
“…It has been reported that vitamin D, zinc, glutamine, and other nutrients exhibit beneficial effects and are promising as a therapeutic option for COVID‐19. [ 26,27 ] Among the huge number of metabolites, amino acids play essential roles in regulating the homeostasis of immune responses. [ 41,42 ] In this study, metabolic pathways commonly up‐regulated in asymptomatic and remission patients included arginine biosynthesis, alanine, and glutamate metabolism, in which l ‐citrulline, l ‐glutamine, and l ‐alanine were the most significant metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The only paper that discussed oxygen supply, demand, or related infrastructure was by Amira K Al-Aamri et al, which forecasted the critical care resources threshold in the Gulf Cooperation Council (GCC) countries. ( 13 ) The paper predicted the number of critical cases requiring oxygen, among many other parameters estimated using the WHO Adaptt Surge Planning Tool. ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specific smartphone applications were employed to communicate between the health authorities and the public, and a work-from-home system was adopted [48,49]. Moreover, treatment, quarantine, screening services, and vaccines were offered freely even for the residence violators, along with stabilizing food and medical commodities' levels and market prices [16,[50][51][52][53][54]. In addition, at the time of our survey, the number of COVID-19 cases and deaths in UAE, KSA, Bahrain and Kuwait was over 520,000 cases (5.2% of population ~ 10 million) with 1590 deaths (0.3%), 418,000 cases (1.2% of population ~ 35.4 million) with 7000 deaths (1.7%), 178,000 cases (9.9% of population ~ 1.8 million) with 648 deaths (0.4%), and 275,000 cases (6.5% of population ~ 4.2 million) with 1570 deaths (0.6%), respectively [24].…”
Section: Discussionmentioning
confidence: 99%